Reassessing the ESP course offering to Engineering Students: identifying correspondences between the course contents and workplace language needs (Case Study of Students of College of Engineering at Majmaah University, K.S.A) - Bashir, Ishraga; Fouad, Ehab (Advances in Social Sciences Research Journal, 2017)
English is needed and is used extensively in the field of engineering and work. One more important point is that Graduates from Saudi Universities are likely to face difficulties coping with communication in positions in which the working language is English. This is not only because the amount of time and their exposure to English are insufficient, but also because the courses offered do not prepare them adequately for the job market. This research presents the steps for conceiving an acceptable curriculum that would enable identifying specific workplaces in which the language of communication is English. It is widely recognized that a high percentage of today’s school leavers find themselves unemployed due to lack of relevant skills and qualifications and low educational attainment.